2009
DOI: 10.3748/wjg.15.2644
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of patients by family history with gastric and non-gastric cancer

Abstract: AIM:To compare the gastric cancer (GC) patients by their family history with gastric and non-GC. METHODS:Positive family histories within seconddegree relatives and clinicopathological features were obtained for 256 patients. RESULTS:Of the 256 probands, 112 (76 male, 36 female) were incorporated into familial GC (FGC) group: at least two GC members; 144 (98 male, 46 female) were included in the non-FGC group (relatives only affected with non-GCs). Of 399 tumors in relatives (181 from FGC against 212 from non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
3
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
3
0
Order By: Relevance
“…In this study, a positive family history was significantly associated with intestinaltype GC, but not with diffuse-type GC (Tables 4 and 5), which is consistent with the findings of an Italian study [44]. However, the frequency of the histological type of GC, with respect to the family history of GC, has varied with different studies [45]. For example, one study reported familial clustering of hereditary diffuse GC in a large cohort of GC in Italy.…”
Section: Discussionsupporting
confidence: 90%
“…In this study, a positive family history was significantly associated with intestinaltype GC, but not with diffuse-type GC (Tables 4 and 5), which is consistent with the findings of an Italian study [44]. However, the frequency of the histological type of GC, with respect to the family history of GC, has varied with different studies [45]. For example, one study reported familial clustering of hereditary diffuse GC in a large cohort of GC in Italy.…”
Section: Discussionsupporting
confidence: 90%
“…Our study population from north of China had the highest amount of associated tumors in the esophagus (26.2%), followed by the stomach (23.8%). The report cited above, using GC patients from south of China, found notably different percentages of stomach- and esophagus-associated tumors (38.6% and 18.3%, respectively) [15]. In contrast, the study of Japanese GC patients found that 40.9% of associated tumors were located in the stomach [11], while the study of Italian GC patients found that only 21.9% of associated tumors were located in the stomach [10].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the association was more pronounced among those diagnosed with gastric cancer at a younger age and born later. There are several potential explanations for these results, one possibility is that these individuals may have a stronger genetic predisposition to gastric cancer, which is compounded by a common environment shared within the family [ 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%